Studies on Clinical Features, Mechanisms, and Management of Olfactory Dysfunction Secondary to Chronic Rhinosinusitis - Lin, Yi-Tsen; Yeh, Te-Huei (Frontiers in Allergy, 2022)
Chronic rhinosinusitis (CRS) is one of the most common causes of inflammation of the olfactory system, warranting investigation of the link between chronic inflammation and the loss of olfactory function. Type 2 inflammation is closely related to the clinical features and disease mechanisms of olfactory dysfunction secondary to CRS. Patients with eosinophilic CRS, aspirin-exacerbated respiratory disease, and central compartment atopic disease report increased olfactory dysfunction. Increased levels of interleukin-(IL-)2, IL-5, IL-6, IL-10, and IL-13 in the mucus from the olfactory slit have been reported to be associated with reduced olfactory test scores. The influence of several cytokines and signaling transduction pathways, including tumor necrosis factor-α, nuclear factor-κB, and c-Jun N-terminal kinases, on olfactory signal processing and neurogenesis has been demonstrated. Corticosteroids are the mainstay treatment for olfactory dysfunction secondary to CRS. Successful olfaction recovery was recently demonstrated in clinical trials of biotherapeutics, including omalizumab and dupilumab, although the treatment effect may diminish gradually after stopping the use of the medications. Future studies are required to relate the complex mechanisms underlying chronic inflammation in CRS to dysfunction of the olfactory system.